Treatment-Resistant Depression: The Role of Electroconvulsive Therapy - Kupis, Magdalena; Paszkowska, Monika; Znamirowska, Patrycja; Mularczyk, Klaudia; Karaban, Łukasz; Jakubiak, Anna; Miśkiewicz, Joanna; Borawski, Michał; Ciuła, Aleksandra; Kuźnieców, Tadeusz (Quality in Sport, 2025)
Introduction and purpose: Depression remains the leading cause of disability worldwide, affecting the lives of nearly 300 million people. A particularly severe form of depression is treatment-resistant depression (TRD), which is associated with significant health, social, and economic problems. Its prevalence varies due to the lack of a unified definition. This paper reviews the efficacy and safety of electroconvulsive therapy (ECT) in the treatment of TRD. Material and methods: A comprehensive search of the PubMed database was conducted to identify studies published between 2015 and 2025 that focused on electroconvulsive therapy in the context of treatment-resistant depression. The search strategy included keywords such as “electroconvulsive therapy,” “treatment-resistant depression”, “safety of electroconvulsive therapy.’’ Relevant articles were reviewed and evaluated based on the reported outcomes and the authors’ conclusions. A brief description of the state of knowledge: Treatment-resistant depression (TRD) affects a great number of patients diagnosed with major depressive. Effective management of TRD requires appropriate pharmacotherapy, careful diagnostic evaluation and consideration of patient adherence. Electroconvulsive therapy (ECT) appears to be the most thoroughly researched and clinically effective method, particularly in severe cases and in populations at higher risk, such as older adults and pregnant women. Conclusions: ECT remains one of the most effective treatment alternatives for TRD, especially in patients with severe symptoms or psychotic features. Choosing between these treatments should be guided by clinical context, patient characteristics, and personal preferences. Equally important is the need to continue working on breaking the stigma around mental health conditions and ECT, by raising awareawareness, educating people, and ensuring everyone has equal access to safe and effective treatment.